Augmented Package of Palliative Care for Women With Cervical Cancer: Responding to Refractory Suffering. (2021) - Krakauer, Eric L.; Kane, Khadidjatou; Kwete, Xiaoxiao; Afshan, Gauhar; Bazzett-Matabele, Lisa; Ruthnie Bien-Aimé, Danta Dona; Borges, Lawrence F.; Byrne-Martelli, Sarah; Connor, Stephen; Correa, Raimundo; Devi, C. R. Beena; Diop, Mamadou; et al.
Abstract : The essential package of palliative care for cervical cancer (EPPCCC), described elsewhere, is designed to be safe and effective for preventing and relieving most suffering associated with cervical cancer and universally accessible. However, it appears that women with cervical cancer, more frequently than patients with other cancers, experience various types of suffering that are refractory to basic palliative care such as what can be provided with the EPPCCC. In particular, relief of refractory pain, vomiting because of bowel obstruction, bleeding, and psychosocial suffering may require additional expertise, medicines, or equipment. Therefore, we convened a group of experienced experts in all aspects of care for women with cervical cancer, and from countries of all income levels, to create an augmented package of palliative care for cervical cancer with which even suffering refractory to the EPPCCC often can be relieved. The package consists of medicines, radiotherapy, surgical procedures, and psycho-oncologic therapies that require advanced or specialized training. Each item in this package should be made accessible whenever the necessary resources and expertise are available.